Spatial Differencing Reconstruction Based Low-Angle DOA Estimation with MIMO Radar - Zhang, Qin; Zhang, Linrang; Shi, Junpeng; Zhou, Yannian; Liu, Yaning (Xibei Gongye Daxue Xuebao/Journal of Northwestern Polytechnical University, 2018)
Due to the multipath effect, the direction of arrival (DOA) estimation performance for low-angle targets decreases greatly. To overcome this problem, this paper proposes a spatial differencing reconstruction based DOA estimation algorithm by using the received signal model of multiple input multiple output (MIMO) radar. Combining with the spatial diversity of MIMO radar, the proposed method can first use the multipath echo power to select the best signal. Then, a spatial differencing based iterative scheme is developed to reduce the effect of additive noise, resulting in a better estimation performance for low-angle targets. Simulation results show that the proposed method has better advantages in suppressing noise and improving estimation accuracy. 用雷达系统探测低空和超低空目标时，角度估计性能会因多径效应的影响而下降。针对这一问题，通过建立低空多径环境下MIMO雷达阵列接收信号模型，提出了一种基于空间差分重构的DOA估计方法；首先利用空间分集特性，对多径回波能量进行回波信号优选；通过空间差分迭代计算进一步降低噪声对估计精度的影响，较好地实现了对低空目标的DOA估计。仿真验证的结果表明该方法在抑制噪声干扰、提高估计精度方面，具有较大的优势。